Правители России от Юрия Долгорукого до наших дней: ежегодный справочник по истории России / Е. В. Пчелов, В. Т. Чумаков - Пчелов Евгений Владимирович (Грантъ, 1999)
Экземпляры: (20160421) / Инвентарный номер: 35752 / Цена: / Сис.шифр: 63.3(2Р) / Авт.знак: П92 / ББК: 63.3(2Р)